(untitled) (Medicine Today, 2015)
Among possible pathogenic and adaptive mechanism of acute myocardial infarction and development of its complications, the system of prostanoids, particularly prostacycline-thromboxane system is of prime importance. But many questions relating the role of prostacycline-thromboxane system in pathogenesis of myocardial infarction associated with heart failure have studied insufficiently. The objective of this work is to study the ststus of prostacycline-thromboxane system in patients of acute myocardial infarction associated with heart failure and its correlation with the platelet functions depending on stages of heart failure. This study was performed in the department of Internal Medicine in Kharkov State Medical Institute, Ukraine in 1985-89. 120 patients with acute myocardial infarction leading to heart failure were studied. The status of prostacycline-thromboxane was considered by the level of stable metabolites of prostacycline and thromboxane - A2 as 6-keto-PGF and TXB2 respectively in venous plasma. 6-Keto-PGF-1a and TXB2 levels were determined by Radio-immunological method with the help of kits manufactured by the English Firm "New England Nuclear". To determine the platelet aggregation properties, the instrument "Bian-120" transmitter was used. It was established clinically that prostacycline- thromboxane activation depends on clinical features of myocardial infarction, i.e. its localization, depth, extension or affected size of MI, first attack or re-infarction. Maximum changes of prostacycline thromboxane system took place in extensive myocardial infarction which was expressed in increased level of TXB2 and significant change of prostanoid imbalance ratio. Parameters of platelet aggregation function and prostacycline thromboxane system were interrelated during heart failure, which were expressed by their changes in aggregation diagram. Medicine Today 2014 Vol.26(2): 83-87